Successful Treatment of a Left Gastric Artery Pseudoaneurysm by Image Guided Percutaneous Thrombin Injection. (April 2023) - Thomson, Benedict; Patel, Virjen; Moser, Steven; Diamantopoulos, Athanasios
Visceral artery pseudoaneurysms are common complications of pancreatitis that carry a high mortality rate. The splenic artery is the commonest artery involved. Gastric artery pseudoaneurysms are less common with less than 50 cases reported in the literature. A 58-year-old female was referred to the Interventional Radiology department with a left gastric artery pseudoaneurysm secondary to acute pancreatitis. Initial Digital Subtraction Angiography revealed the pseudoaneurysm arising from the left gastric artery. Several attempts to cannulate the pseudoaneurysm were unsuccessful due to arterial spasm. Consequently, the left gastric artery proximal to the pseudoaneurysm was embolised with 300 microns of polyvinyl alcohol and two coils. 24 hours post-procedure, a computed tomography (CT) scan was performed which revealed a blush of contrast enhancement within the pseudoaneurysm sac, consistent with unsuccessful embolisation. Using a combination of ultrasound and cone beam CT guidance, a 22-gauge Chiba needle was advanced percutaneously via a transhepatic approach to the patent segment of the pseudoaneurysm. 2.5 ml of human thrombin was then injected directly into the pseudoaneurysm. Image guided injection of thrombin has become a well-recognised treatment for a variety of peripheral and visceral pseudoaneurysms and is often performed following a failed attempt of routine endovascular embolisation. We report the case of a patient affected by a pseudoaneurysm of the left gastric artery, treated with a CT guided percutaneous thrombin injection directly into the pseudoaneurysm. This demonstrates that percutaneous coagulation can be an adjunct or an alternative to endovascular embolisation.